Physical Activity and Overnutrition Among 8–11-Year-Old School Children in Thika Town, Kenya - Margaret Wanjiru Mburu; Peninah Kinya Masibo; Anselimo Makokha; Shehu Shagari Awandu; Patrick Opiyo Owili (Journal of Nutrition and Metabolism)
Conclusion: There is a presence of overnutrition in school children in Thika town, Kenya. The same population is also undernourished, thus demonstrating the double burden of malnutrition. Almost half of the children were physically inactive. An integrated approach to early detection, prevention, and management of malnutrition in children aged 5–19 years is needed. These findings have implications for public health interventions in preventing childhood obesity. Interventions could prioritize encouraging physical activity through school-based education, improvement of community infrastructure, and policy approaches. Multisectoral collaboration can create solutions that encourage active commutes with general obesity prevention.